Quality of Life Using General Population Validated Questionnaires in Children With Cleft Lip and/or Palate in New Zealand. (June 2021) - Thompson, John M. D.; Ayrey, S. Louise; Slykerman, Rebecca F.; Stone, Peter R.; Fowler, Peter V.
Objective: To determine the level of quality of life (QoL) in children with cleft lip and/or palate (CL/P) and whether this differs by cleft phenotype. Design: A cohort of children with CL/P born in New Zealand. Setting: A nationwide study of children born with CL/P and having primary surgery in New Zealand. Participants: Children with CL/P and their families (n = 397) who attended a cleft clinic between October 1, 2014, and September 30, 2017, and agreed to complete questionnaires on QoL. Main Outcomes: Primary outcomes were QoL from the PedsQL 4.0 core generic questionnaires and the PedsQL 2.0 Family impact scale. Results: Children with CL/P in New Zealand generally have a high QoL as assessed by the PedsQL. The impact of cleft phenotype had limited effects on the child, however there were significant impacts on parents and families. We found that the family impact scale differed by cleft phenotype with those with CL having the highest QoL and those with cleft palate the lowest, and this was consistent across QoL subscales. Quality of life improved as a whole by age, particularly in physical and cognitive functioning, as well as in the ability to undertake family activities. Conclusions: Children with CL/P have generally good levels of QoL in New Zealand, however cleft phenotype impacts on the level, with the lowest levels in those with cleft palate. Psychological support of children with cleft and their families should be an integral part of cleft care.